Occupational Heterogeneity and Labor Force Reproduction: The Cases of Argentina and Mexico - Poy, Santiago; Montoya-García, María Valeria Judith (Sociedad y Economía, 2023)
This article analyzes inequalities in the processes of socioeconomic reproduction of the labor force in relation to socio-occupational heterogeneity. For this purpose, it considers the socio-demographic and labor behaviors of working households, taking Argentina and Mexico as case studies. The hypothesis is that economic-occupational heterogeneity originates processes of structural inequality in the living conditions of the labor force, expressing itself in deficient capacities for material reproduction, which would not be independent of the reproductive behaviors displayed by households. The sources of information were the Permanent Household Survey (Encuesta Permanente de Hogares, EPH) of Argentina and the National Occupation and Employment Survey (Encuesta Nacional de Ocupación y Empleo, ENOE) of Mexico. Descriptive statistical techniques were applied together with a binary logistic regression model. The results suggest that occupational heterogeneity in the countries analyzed plays a determining role in the unequal material reproduction capacities of the household labor force.